Demography, the study of human population - Yaukey, David; Anderton, Douglas L.; Lundquist, Jennifer Hickes (Long Grove, Ill. : Waveland Press, 2007)
"The third edition of Demography features up-to-date information on the study of the causes of changes in size and composition and the effects of these population trends. Like its predecessor, this expanded third edition is written in a reader-friendly style, featuring a wealth of newly enhanced graphics, examples, exercises, and data. Its international focus offers updated, substantive discussion of long-term trends and projections, along with newly emerging topics of interest to demographers. End-of-chapter exercises and propositions for debate bring demography alive for readers and emphasize demography's relevance and importance in the twenty-first century."--BOOK JACKET.
1. Introduction -- 2. Demographic data -- 3. Population growth -- 4. Age and sex structure -- 5. Mortality -- 6. Morbidity and health -- 7. Fertility -- 8. Marriage and householding -- 9. Migration -- 10. Urbanization -- 11. Population diversity.
Includes bibliographical references and index.
Keywords: Demography; Demography; Demografie